Analysis of serum ascites albumin gradient (SAAG) in cats with hepatic disorder - Sudhakara Reddy, Bhavanam; Kambala Swetha; Sirigireddy Sivajothi (Indian Journal of Veterinary Medicine, 2024)
Three Persian breed cats were diagnosed to be having hepatitis. Clinical examination revealed dullness, dehydration, poor body condition and fluid thrill on the abdominal palpation. Radiography and ultrasonography revealed ground glass appearance of the abdomen and anechoic fluid in the abdomen respectively. Elevated serum ascites albumin gradient with elevated serum alanine transaminase levels were noticed in these cats